(untitled) (Iter, 2022)
Attic tragedy deals with myths, pa rticu la rly th e ones in the Theban and Trojan Cycles, in order to make one reflect on highly topical subjects in Greek society at that time, and on troubles affecting man in general. Different expressions of political power are present in Aeschylus’ oeuvre, an d despite claims always made that Sophocles shifts attention to the individual a n d family, works like Antigone and even Oedipus have made a great impact on rethinking tyrannical power later. However, there are only a very few modern works being based on Sophocles’Ajax, and the critics usually study the tragedy, focusing on other aspects. That is why it is very significant that the Cuban playwright Reinaldo Montero -whose version of Medea made him famous in 1996, after winning the Italo Calvino Prize, and who wrote his own version of Antigone in 2009- revisited the Trojan myth and Sophocles’tragedy in order to write his Ajax in 2013 that was just premiered in 2016 by the name of Ajax and Cassandra . By means of figures established by that important event in Greek mythology, and by Attic tragedy, Montero brings to light a highly topical subject regarding secrets had and wiles used by power holders, by stressing the role played by poetry in the past and by mass media nowadays, and shows how today’s culture has received classical antiquity.